Features of Dramaturgy of Ptushkin’s Piano Suite “Theater Kaleidoscope” - Herdova, Tetiana; Mitlytska, Viktoriia (Journal of History Culture and Art Research, 2019)
The problems of the art wholeness of musical composition are actual for both composer’s and performer’s creative work. The article suggests the study of V. Ptushkin’s “Theater Kaleidoscope” piano suite, its drama peculiarities as one of the possible variants of the problem solution. Genre-historical ties and music-genre panorama of the Ptushkin’s cycle are analyzed in the article. The drama suite features in the author’s application of everyday life dances are described in this publication. The Waltz peculiarities as genre basis drama in the third cycle part are analyzed. The role of two types of drama in the formation of the artistic integrity of the suite is studied on reasonable and objective criteria. The novelty of the suggested problem is in the definition of its genre-historical ties with the ancient chamber suite and with the commedia dell’arte. It also involves the value of a dramatic suite type as the main organizing principle of the entire cycle. The “event”, lyric-dramatic type of the dramaturgy in the third suite part is based. The connection of the inner dramaturgy of the third part and the structural organization of the artistic wholeness are determined. This is the basis of the ternary in the entire cycle. The role of the fourth part as the final and the original reprise returning of the drama suite type are noted.